Between Forced Gratitude, Rejection, and Coercion: Colonial Workers during World War I - (:unkn) unknown (My University, 2008)
Imported from Africa or Asia, more than 220 000 immigrant workers participated in the war effort from 1915 to 1919. Framed in an almost military way, kept away from the local population, they have been employed in the aim of achieving the highest performance and of being confined to a strict obedience. Once their presence was no longer necessary, they were rapidly sent back to their countries of origin.
Keywords: African Research